The Principal's Policy Efforts In Improving The Character Education Of The Students Of Upt SDN 009 Trimanunggal Tapung District - Kasnawi, Kasnawi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to get an overview of character education, find out about the program and its implementation and find out the factors and how to try to improve the obstacles at SDN 009 Trimanunggal. This research uses field research which is descriptive qualitative in nature. The data collection techniques use interview, observation, documentation and triangulation methods. Meanwhile, data analysis techniques use data reduction, data presentation, drawing conclusions. The subjects in this research were the principal of SDN 009 Trimanunggal, Deputy Head of Curriculum, PKN Teacher. The results of this research show that: 1) The principal's policy at SDN 009 Trimanunggal in improving character education is programs that are filtered from the opinions of teachers and students. 2) SDN 009 Trimanunggal has superior programs, namely increasing National Examination (UN) scores with a target of 90.20, tahfidz Qur'an, developing 5 foreign languages (Japanese, Korean, Mandarin, Arabic and English) , TOEFL guidance for class IX. 3) for evaluation, namely by having a morning assembly which is held before learning begins. This morning's call serves to find out whether programs or activities (academic or non-academic) are running well without any obstacles